Monitoring tunnel liners using fibre optic sensors - Wiyata Sadikin (Nanyang Technological University, 2022)
The issue of Structural Health Monitoring (SHM) is gaining importance as a means of assessing the health of a structure by determining the amount of degradation and evaluating the remaining service life of civil infrastructure systems. The successful field implementation of SHM has not been widely achieved and is contingent upon overcoming several obstacles, namely the development and demonstration of SHM sensors with long-term stability and reliability, and the validation of the capability of SHM systems in terms of the probability of flaw detection.